Diagnosis Penyakit Hati Menggunakan Metode Naive Bayes Dan Certainty Factor - Rhyzoma Grannata Rafsanjani; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Liver disease or liver disease is a disease caused by various factors that damage the liver, such as viruses and alcohol use. Obesity is also associated with liver damage. Over time, liver damage can cause serious effects, the presence of experts will be very helpful in dealing with liver disease problems by identifying the symptoms experienced and infer what type of liver disease is attacking and provide information to deal with the problem. The Naive Bayes method is a method used to predict probabilities. While Certainty Factor is a method that can help experts who diagnose something uncertain. Variables needed in this study are symptoms of liver disease and liver disease type. Based on the results of testing and analysis of the results of this study, it can be taken some conclusions that Method Naive Bayes and certainty factor can be used for the diagnosis of liver disease. The Naive Bayes method and certainty factor resulted in an accuracy of 88%.